Ageproof : living longer without running out of money or breaking a hip - Chatzky,Jean Sherman (Grand Central Life & Style, 2017)
All the money in the world doesn't mean a thing if we can't get out of bed. And the healthiest body in the world won't stay that way if we're frazzled about five figures worth of debt. Today Show financial correspondent Jean Chatzky and the Cleveland Clinic's chief wellness officer Dr. Michael Roizen explain the vital connection between health and wealth, giving readers the tactics, strategies, and know-how to live longer, healthier, more lucrative lives. The same principles that allow us to achieve a better body will allow us to do the same for our investment portfolio. For instance, physical and financial stability comes down to the same equation: Inflow versus outflow. Do we burn more calories than we ingest? Likewise, are we making more money than we spend? The authors detail ways to improve behavior so that the answers tilt in the readers' favor. They also offer ways to beat the system by automating how we do things and limiting our decisions in the face of too much food or too much debt.